2018
DOI: 10.17706/ijbbb.2018.8.4.226-236
|View full text |Cite
|
Sign up to set email alerts
|

Process Mining in Cardiology: A Literature Review

Abstract: Process mining is a data analytics approach which has shown promising results in healthcare including the potential to improve the management of chronic diseases such as cardiovascular disease (CVD). CVD are one of the leading causes of premature death worldwide. Helping healthcare professionals develop a better understanding of how to improve CVD care pathways may result in better outcomes for patients. This paper describes the opportunities for process mining to support such improvements and provides a summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Event log analyses using the descriptors show pathway differences between stroke, infarctus, amputation and TKCD. Indeed, the first two complications are characterized by shorter traces (|σ| q1,m,q3 : (1,3,4) and (2,3,5) vs. (3,5,8) and (4,6,9)), that is to say short and unstructured pathways compared to the other two. This difference between complications is also highlighted by the best final replayability scores: amputation and TCKD have lower scores (R T G : 0.75 and 0.70) compared with those of stroke and infarctus (0.87 and 0.86) because longer and more complex pathways are less easily replayed in a graph than shorter ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Event log analyses using the descriptors show pathway differences between stroke, infarctus, amputation and TKCD. Indeed, the first two complications are characterized by shorter traces (|σ| q1,m,q3 : (1,3,4) and (2,3,5) vs. (3,5,8) and (4,6,9)), that is to say short and unstructured pathways compared to the other two. This difference between complications is also highlighted by the best final replayability scores: amputation and TCKD have lower scores (R T G : 0.75 and 0.70) compared with those of stroke and infarctus (0.87 and 0.86) because longer and more complex pathways are less easily replayed in a graph than shorter ones.…”
Section: Resultsmentioning
confidence: 99%
“…Since the later systematic review on healthcare, new process mining contributions applied to healthcare have been proposed. Kusuma et al compiled a literature review of process mining in cardiology [5]. Promising opportunities to assist medical experts in care analysis were shown, although few formal process mining methodologies were included.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first stage covered the search of papers from medicine, technology and engineering databases; PubMed, Medline, British Medical Journal Open, ACM DL, Elsevier, ScienceDirect, database systems and logic programming (DBLP), Web of Science and Google Scholar. Keywords for process mining replicated those used in previous literature reviews (Kurniati et al, 2016;Kusuma et al, 2018). To ensure the search obtained papers that cover all relevant conditions related to older people a broad selection of keyword terms was applied following the Medical Subject Headings (MeSH) terms used in the PubMed and Medline databases.…”
Section: Search Processmentioning
confidence: 99%
“…There are a number of recent literature reviews of process mining in healthcare (Rojas, 2016;Erdogan and Tarhan, 2018;Williams et al, 2018) and other reviews which focus on specific healthcare specialties such as cancer (Kurniati et al, 2016) and cardiovascular disease (Kusuma et al, 2018). However, until now there has been no literature review specifically examining process mining for the care of the frail elderly.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, process mining techniques have been used to conduct a comparative analysis of patients' care pathways in four South Australian Hospitals [2], and to undertake performance analysis of patients' length of stay [3]. Insights from these studies and many others [4][5][6] showed potential benefits of utilising process mining techniques in the healthcare domain while also highlighting many challenges associated with varying quality of healthcare data [4,7,8] and the complexity of modelling healthcare processes where variations are the norm rather than the exception. There are several novel and challenging aspects to this study.…”
Section: Introductionmentioning
confidence: 99%